2009
DOI: 10.3945/jn.108.096446
|View full text |Cite
|
Sign up to set email alerts
|

(n-3) Fatty Acid Content of Red Blood Cells Does Not Predict Risk of Future Cardiovascular Events following an Acute Coronary Syndrome

Abstract: A reduced risk of fatal coronary artery disease has been associated with a high intake of (n-3) fatty acids (FA) and a direct cardioprotective effect by their incorporation into myocardial cells has been suggested. Based on these observations, the omega-3 index (eicosapentaenoic acid + docosahexaenoic acid in cell membranes of RBC expressed as percent of total FA) has been suggested as a new risk marker for cardiac death. In this study, our aim was to evaluate the omega-3 index as a prognostic risk marker foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
3
25
1
2
Order By: Relevance
“…21,23,46,47 Another case-control study, however, could not confirm this finding. 48 Red blood cells were not available for analysis in this study, so we were unable to provide further information on this issue.…”
Section: Joensen Et Al N-3 Fatty Acids and Acute Coronary Syndromementioning
confidence: 94%
“…21,23,46,47 Another case-control study, however, could not confirm this finding. 48 Red blood cells were not available for analysis in this study, so we were unable to provide further information on this issue.…”
Section: Joensen Et Al N-3 Fatty Acids and Acute Coronary Syndromementioning
confidence: 94%
“…Thus, dietary supplementation with fi sh oil (C 20-22 3 PUFA), but not dietary fl axseed (ALA), signifi cantly increases cardiac muscle C 20-22 3 PUFA content. Such studies suggest that the omega-3 index may be a reasonable approach to assess cardiac 3 PUFA content and predict future CVD events ( 26,27 ). Sudden cardiac death (SCD), for example, is estimated to account for 50% of all deaths from CHD (28)(29)(30).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Several studies of measured EPA and DHA in patients with ACS have been reported, with mixed findings (Table 3). In one study of patients admitted for ACS (n = 460) and followed for 2 years, EPA and DHA (measured in whole blood) showed a trend between low concentrations of EPA and DHA and CV mortality; however, it was not significant [51]. A larger study (n = 1536) of patients enrolled in the TRIUMPH registry found that EPA and DHA (measured in erythrocyte membranes) added significantly to the GRACE score in predicting 2-year mortality [52].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 94%